EVALUASI DINAMIKA STRUKTUR PADA BALOK KANTILEVER FIX- FREE DENGAN MENGGUNAKAN ANALISA METODE ELEMEN HINGGA - Siagian, Tony; Derlini, Derlini; Misdawati, Misdawati (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2025)
This study aims to evaluate the characteristics of the dynamic load that occurs on the beam clamped at one end and the other end in a free condition. At one end of the rod a load is given so that it will cause a larger dynamic load on the rod. The method used to analyze the dynamics of this cantilever rod structure uses the Finite Element Method. The cantilever rod will be divided into four elements and has 10 nodal points, vibrating nodes are occured at node 3 until node 10. By using stiffness and mass matrix analysis, found that the largest deflection value is obtained at node 9 with a deflection value of 0.2555 m and the largest angular rotation occurs at node number 10, which is 0.0958 rad. By assuming the weight of the cantilever bar is ignored, the reaction at the clamped rod support is obtained equal to the magnitude of the load given at node 9 in the opposite direction to keep the rod prevent from falling, which is -100 N. The farer distance of nodal point from the end of the bar that is given the load then the smaller the deflection that occurs, including the angular rotation will also be smaller. The selection of beam materials, beam dimensions, beam installation methods and determination of the external load greatly determine the safety factor of the cantilever beam construction.